POMODORO TECHNIQUE FOR IMPROVING STUDENTS’ READING ABILITY DURING COVID-19 PANDEMIC - Kisno . (Institut Pendidikan Tapanuli Selatan, 2020)
Covid-19 pandemic changes the teaching-learning patterns and processes in most of educational institution in Indonesia. The duration of learning process has been a vital factor during study from home since students are not burdened with full-day attendance anymore. This paper aims to investigate how Pomodoro Technique improved the students’ reading ability during study from home. This study implemented a quasi-experimental design involving sixty students of both Management and Accounting Study Programs in English subject. Half of the students was taught using Pomodoro Technique for time management and the other was taught using continuous duration as was scheduled in timetable. Pre- test and post-test were used as the instrument for collecting the data and the students’ score was analyzed with independent t-test sample using Mx. Excel 2019. The finding showed that the result of independent t-test on post-test score was 0.0000 which means that the significance value was lower than 0.05 (0.000 > 0.05) and the average of the students’ score using Pomodoro Technique increased significantly. To conclude, the Pomodoro Technique for time management could be recommended as one of the efficient time-management techniques in improving the students’ reading ability during the period of study from home.